Interpreting Emotions From Women With Covered Faces: A Comparison Between a Middle Eastern and Western-European Sample - Kret, Mariska E.; Maitner, Angela T.; Fischer, Agneta H. (Frontiers in Psychology, 2021)
The question whether face coverage has an effect on interpersonal emotion communication has become more pressing now that the pandemic has resulted in the recommendation or obligation of wearing mouth masks in many countries in the world. Previous research on the effects of wearing veils or face-covering niqabs showed that covering of the mouth has lead to the attribution of negative emotions and to the perception of less intense positive emotions. The current study compares a sample from the Netherlands with the United Arab Emirates (UAE) on their perception of emotions from faces covered by a niqab, censoring black bars, or uncovered faces. The results show that covering the mouth area leads to greater anxiety in participants in both countries. Furthermore, although participants did not report greater decoding difficulties for faces that were covered as compared to fully visible, results show that face coverage did influence emotion perception. Specifically, happiness and anger were perceived less intensely. Further, face coverage by a niqab as compared to black bars yielded lower emotional intensity ratings. We conclude that face coverage in particular can modulate the perception of emotions, but that affective contextual cues may play a role as well.